2013
DOI: 10.1016/j.jor.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of unstable distal third clavicular fracture with locked distal radius plate

Abstract: Fracture Surgery Internal fixationLocked plate a b s t r a c t Background: The ideal surgical fixation for displaced distal clavicle fractures should not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Martetschläger et al, in a study of 30 patients who were managed with a Synthes T plate and additional coracoclavicular-ligament augmentation with use of polydioxanone (PDS) suture, reported that 40% of the patients experienced implant-related pain that necessitated subsequent implant removal 26 . It may be argued that this plate has different characteristics and is thicker than the plates used by Hohmann et al 25 and Abdeldayem et al 24 , which could explain the discrepancy in the rate of implant-related complications. Otherwise, the outcomes were very similar to those reported by Hohmann et al 25 Tension band wiring has been successfully used for the treatment of patellar and olecranon fractures, but only a few reports have described the use of this technique for the stabilization of distal clavicular fractures (Fig.…”
Section: Distal Radial Platesmentioning
confidence: 90%
See 1 more Smart Citation
“…Martetschläger et al, in a study of 30 patients who were managed with a Synthes T plate and additional coracoclavicular-ligament augmentation with use of polydioxanone (PDS) suture, reported that 40% of the patients experienced implant-related pain that necessitated subsequent implant removal 26 . It may be argued that this plate has different characteristics and is thicker than the plates used by Hohmann et al 25 and Abdeldayem et al 24 , which could explain the discrepancy in the rate of implant-related complications. Otherwise, the outcomes were very similar to those reported by Hohmann et al 25 Tension band wiring has been successfully used for the treatment of patellar and olecranon fractures, but only a few reports have described the use of this technique for the stabilization of distal clavicular fractures (Fig.…”
Section: Distal Radial Platesmentioning
confidence: 90%
“…Three studies have evaluated the use of distal radial plates for the fixation of lateral clavicular fractures [24][25][26] (Table III). Distal radial locking plates are generally smaller and thinner than contoured locking plates and therefore should presumably cause less subcutaneous implant irritation (Fig.…”
Section: Distal Radial Platesmentioning
confidence: 99%
“…The functional and radiological outcome achieved was satisfactory to the patient with no complications. Ashraf et al studied the results of internal fixation with distal radius volar plate on fifteen patients [ 7 ]. Thirteen patients achieved full range of motion and the other two had minor limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Type V is similar to type II, which involves an avulsion leaving behind an inferior cortical fragment attached to the coracoclavicular ligament [ 2 ]. Initially, Neer suggested using trans-acromial Kirschner wire to stabilise the fracture; however, over the years, several different surgical techniques have been developed for the fixation of the lateral end clavicle fractures [ 3 ]. A recent review by Sambandam et al [ 2 ] discussed different fixation methods.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by Sambandam et al [ 2 ] discussed different fixation methods. These include pre-contoured locking plates [ 4 ], hook plates [ 5 ], distal radius plates [ 3 ], coracoclavicular screws [ 6 ], flexible coracoclavicular fixation [ 7 ] and intramedullary fixation [ 8 ]. However, these techniques were also accompanied by multiple disadvantages, including wire migration, failure of fixation, irritation of soft tissues, including the rotator cuff, infection, fractures and osteoarthritic changes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%